2007
DOI: 10.1002/tal.415
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of tall buildings under wind: insights from full‐scale monitoring

Abstract: SUMMARYThe wind-induced response of tall buildings is inherently sensitive to structural dynamic properties like frequency and damping ratio. The latter parameter in particular is fraught with uncertainty in the design stage and may result in a built structure whose acceleration levels exceed design predictions. This reality has motivated the need to monitor tall buildings in full-scale. This paper chronicles the authors' experiences in the analysis of full-scale dynamic response data from tall buildings aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 10 publications
5
29
0
Order By: Relevance
“…In fact, this finding is entirely consistent with the levels of damping observed in stationary random decrement analyses of low-amplitude sway modes by Kijewski-Correa and Pirnia (2007). That study found that as amplitude levels dropped, these sway modes could show particularly large damping values.…”
Section: Implications Of Dynamic Couplingsupporting
confidence: 88%
See 3 more Smart Citations
“…In fact, this finding is entirely consistent with the levels of damping observed in stationary random decrement analyses of low-amplitude sway modes by Kijewski-Correa and Pirnia (2007). That study found that as amplitude levels dropped, these sway modes could show particularly large damping values.…”
Section: Implications Of Dynamic Couplingsupporting
confidence: 88%
“…The amplitude range canvassed here surpasses previous analyses of this building and confirms the reduction in natural frequency with amplitude initially observed by Kijewski-Correa and Pirnia (2007). Still there is appreciable scatter in these instantaneous frequency estimates, which in part may be attributed to the variance inherent to this system identification method that cannot benefit from averaging, but also to the dynamics of the problem, as the next section will demonstrate.…”
Section: Instantaneous Dynamic Properties From Impulsessupporting
confidence: 84%
See 2 more Smart Citations
“…This form of local averaging has been shown to improve RDT performance by minimizing trigger sensitivity, while still permitting documentation of the degree of amplitude dependence in viscous damping ratios of several tall buildings and the effect of amplitude-dependent frequency on not only equivalent viscous damping, as shown in Figure 1, but also as a facilitator of significant lateral-torsional beat phenomena at modest wind speeds [Kijewski-Correa and Pirnia, 2007].…”
Section: Wind/ambient Vibration Applicationsmentioning
confidence: 99%